A synergistic enzymatic strategy for comprehensive improvement of bread quality and digestibility using a novel maltohexaose-forming amylase and a 4,6-α-glucanotransferase - Yu-chuan Wang; Hong Liu; Li-xiao Fu; Meng-jun Han; Qiao-juan Yan; Zheng-qiang Jiang; Yan-xiao Li (Food Hydrocolloids, 2026)

Assessing multidimensional changes in human settlements across urban regeneration paradigms: A case study of Wuhan, China - Meng-Tian Han; Qian Cao; Hai-Yun Xu; Xiang-Wen Deng; Lun-Che Wang; Jun Wan (Sustainable Cities and Society, 2026)

Structural features of endogenous polyphenols in modulating oxidative stability of tiger nut (Cyperus esculentus L.) oil: Insights from Rancimat and density functional theory - Zheng-Kai Zhang; Meng-Chen Xie; Jun-Chao Zhang; Lu-Han Sun; Xiao-Shuang Cai; Run-Yang Zhang; Guo-Qiang Zhang; Hua-Min Liu (Food Chemistry, 2026)

Fermentation modulates wheat germ gliadin-based nanodelivery systems loaded with wheat bran polyphenols: Physicochemical properties, interaction mechanism, and functional performances - Ai-Mei Liao; Shao-Kang Yang; Meng-Yu Gao; Siyi Han; Long Pan; Jayani Chandrapala; Haiyan Gao; Dandan Zhai; Jun-Wei Chen; Na Liu; Peng Li (Food Bioscience, 2026)

PD-1/PD-L1 inhibition after cryoablation is associated with improved tumor control and immunosuppressive microenvironment remodeling in Lewis lung adenocarcinoma - Qi Liu; Shuo Zhang; Xuxin Chen; Jiao Li; Man Qi; Yongqun Li; Yiwei Ding; Xiaoyu Zhao; Jun Shi; Jiajia Tang; Meng Liu; Xue Wang; et al. (Cryobiology, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Egg Disease in Spodoptera litura (Fabricius) Caused by Aspergillus ochraceus and Its Metabolic Phenotype - Wen-Jie Lei; Yan Zhao; Qin-Ye Zhang; Hao-Jun Wang; Xiang-Li Dong; Jian-Yu Meng; Liu-Ti Cai; Hui-Zi Wu; Han-Cheng Wang (Current Microbiology, 2026)

New cytotoxic p -hydroxybenzoic acid and sesquiterpene-derived amides from Aspergillus fumigatus J2-22-1 - Wenjie Han; Huiying Liu; Meng Ren; Nanxin Gong; Xupei Men; Yurun Wang; Taoshuai Cao; Xiaomei Song; Hongliang Tang; Xiaolong Zhao; Jun Zhang; Du-Qiang Luo (Natural Product Research, 2026)

Ultraviolet-ozone tuned organic-inorganic interface for high-performance PbS quantum dot short-wave infrared photodetectors - Jun Han; Ning Feng; Chuan Wei; Li Yan; Chengrun Shu; Jiatong Liu; Zhouying Wu; Hao Yan; Meili Xu; Yaowu He; Xiaomin Xu; Hong Meng (Chemical Engineering Journal, 2026)

Covalent organic frameworks membrane with gradient hydrophilic channel for moisture-enabled electric generation - Jun Zhang; Jing-Dong Feng; Ruo-Meng Zhu; Yong Liu; Yu-Ou He; Yu-Ting Que; Shuai Geng; Wang-Kang Han; Zhi-Guo Gu (Chemical Engineering Journal, 2026)

Odorous substances released by the flowers of Daucus carota L. attract red imported fire ants (Solenopsis invicta Buren) - Shuai Yu; Hongjing Zhou; Yangming Jiang; Yanju Li; Yonghong Bai; Xiaomei Wu; Ziyi Wang; Meng Lan; Huijun Hu; Kezhan Han; Jun Huang; Yan Li (Arthropod-Plant Interactions, 2026)

Integrated strategy based on Sankey diagram for tracing to odor source apply to the complained industrial park - Jing Wang; Jie Meng; Xiaoyu Ning; Zengxiu Zhai; Xiande Xiao; Jun Zhang; Feifei Zhang; Bo Ma; Meng Han; Zhiyang Zhang; Gen Wang; Qi Zhang (Atmospheric Pollution Research, 2026)

La-mediated green rust for synergistic nitrogen–phosphorus removal and targeted N2 formation regulated by built-in electric field and spin state - Yibo Zhang; Jun Nan; Chen Liang; Zhencheng Ge; Han Deng; Yanhan Che; Yunhao Pan; Meng Li; Bohan Liu (Water Research, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Soil charosphere as a hotspot for antibiotic resistance genes and potential cross-trophic interactions - Wenbo Liu; Xiang Cao; Jun Meng; Yali Kong; Han Gao; Fuyi Huang; Ming Hung Wong; Jin Zhang; Shengdao Shan; Ville-Petri Friman (Journal of Hazardous Materials, 2026)

Differential remediation of tetracycline vs. sulfamethoxazole-contaminated soils by ZVI/BC: Impacts on rice growth, soil properties, and key regulatory factors - Xu Su; Jie Han; Xuanming Wang; Siyu Wang; Yixuan Chen; Ziyi Ge; Jun Meng (Journal of Environmental Chemical Engineering, 2026)

Mechanistic insights into the enhanced degradation of hydroxychloroquine by singlet oxygen in PMS and PMS/Cl2 systems: A comparative study - Zi-Han Feng; Zhen-Zhen Li; Dong-Su Bi; Fu-Xiang Tian; Ling-Yao Meng; Yan-Ting Jia; Yu-Qiong Gao; Xiao-Jun Hu (Journal of Environmental Management, 2026)

Feedstock-dependent nutrient retention and release mechanisms of manure-derived biochars: Implications for mitigating agricultural nutrient loss - Peiyu Luo; Chaoqun Wei; Jing Wang; Kozo Ueda; Xu Yang; Xiaori Han; Jun Meng (Journal of Environmental Management, 2026)

Genetic Diversity of Spodoptera litura in China Based on Mitochondrial DNA Analysis - Yu-Lin Li; Jian-Kun Long; Zhi-Ming Chang; Han-Cheng Wang; Jian-Yu Meng; Lin Yang; Jun-Yi Gao; Xiang-Sheng Chen (Phytoparasitica, 2026)

Plant litter addition promotes short-term improvement of saline-alkali soils through labile carbon and enzyme activities - Lirong Zhao; Yuyang Kou; Mengqi Zhang; Ni Gao; Ermao Ding; Shichen Wang; Kaiyang Han; Yixuan Liu; Minmin Qiang; Huan Ma; Liping Hu; Jun Meng; et al. (Journal of Soils and Sediments, 2026)

System-dependent effects and mechanisms of microplastics/nanoplastics on nitrogen and phosphorus removal from wastewater treatment and N2O emission - Tong Wu; Shuai-Hang Wang; Ping Fang; Cheng-Xin Chen; Jie Ding; Ying He; Han-Jun Sun; Meng-Qi Ding; Ji-Wei Pang; Nan-Qi Ren; Shan-Shan Yang (Journal of Hazardous Materials, 2026)

Alleviating effects and mechanism of Lacticaseibacillus paracasei BHP06 on the allergic reactions induced by ovalbumin - Xiang-Ge Xin; Yue Meng; Jun Meng; Jun Xi; Chang-He Ding; Rui-Han Ge; Yu-Tong Bai; Ming-He Li (Food Bioscience, 2026)

Unlocking potassium sustainability: Rice-crab co-culture system enhances potassium balance - Haixia Liu; Xuran Liu; Feng Zhang; Hongwei Han; Yinghao Li; XiaoLi Wu; Guangyan Liu; Daocai Chi; Jun Meng; Taotao Chen (Field Crops Research, 2026)

Tunnel Micro-deformation Monitoring Method Based on Improved PS-InSAR and Its Geophysical Application Analysis - Meng-wei Han; Gu-hua Pu; Jin-zhuang Wang; Zi-heng Gao; Xiao-qian Yang; Bo Zhang; Ba-he Yang; Jun Ma; Hai-yun Wang; Yong-can Chen; Xi-can Zhao; Wei-jian Liu (Applied Geophysics, 2026)

TRAF7 protects against acute lung injury by promoting K6-linked ubiquitination of AKT - Jia Wang; Meng-Liu Zeng; Ya-Zhou Sun; Xu-Tao Zhang; Xin-Yan Li; Wei-Yi Qu; Wei Li; Jia-Yi Liu; Xu Cheng; Jun Zhang; Han Tian; Hui Liu; et al. (Science Bulletin, 2026)

Nano-bio interaction determines the early progression of lung cancer by reshaping pulmonary epithelial microenvironment - Yu-Han Zhang; Jun Zhang; Lei Shi; Meng Xiang; Xue Han; Ling Zhu; Jia-Cheng Xie; Yan Chen; Qi Gu; Jing-Yu Li; Zhen Zou; Jian-Yu Wang (Journal of Hazardous Materials, 2026)

Global patterns and drivers of canopy storage capacity in different biomes - Meng-Di Wu; Zhi-Yun Jiang; Si-Yi Zhang; Yu-Jun Ma; Shui-Xia Li; Shu-Qin Han; Jin-Zhao Liu (Agricultural and Forest Meteorology, 2026)

Collapse resistance and failure behavior of steel frames under boundary feedback: Interaction-based hybrid simulation - Yu-hui Zheng; Zi-han Wen; Jun Zhao; Bao Meng; Zheng Tan; Yue Zhang (Engineering Structures, 2025)

Vancomycin nanocomposite-functionalized M2 macrophages for precision targeting of MRSA in prosthetic joint infections - Ling Wu; Weijing Cheng; Bingkun Meng; Han Yan; Jun Liu; Fengze Miao; Tingrui Zhang; Xinyue Zhang; Nan Ding; Yujing Zhao; Quangang Zhu; Ziqiang Chen; et al. (Chemical Engineering Journal, 2025)

Valorization of blueberry pomace and red mud to zero valent iron biochar for antibiotic degradation with diminishment of toxic reagents - Xu Su; Jie Han; Yuwei Huang; Xuanming Wang; Siyu Wang; Ziyi Ge; Hechong Yuan; Juying Liu; Xuerong Xiang; Fan Xia; Li Lin; Yu Lan; et al. (Bioresource Technology, 2025)

Endomycorrhizal fungi improve soil nitrogen transformation rates and nitrogen uptake rates of nitrate-preferring plant - Chang Zhao; Shenyan Dai; Shending Chen; Chanjuan Hu; Xiaoqian Dan; Xiaoxiang He; Jun Zhao; Han Meng; Zucong Cai; Jinbo Zhang (Journal of Soils and Sediments, 2025)

Assessment of habitat characteristics in typical seagrass bed ecosystems along the coast of Changhai County, Dalian - Yuchen Chu; Jun Yang; Juncheng Yin; Jie Tian; Jun Song; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; Yanjun Wang; Qian Sun; Quanxiang Meng; et al. (Acta Oceanologica Sinica, 2025)

Study on behavioral preferences, electrophysiological response, and the behavioral active compounds of the essential oils from three edible plants against Solenopsis invicta Buren (Hymenoptera: Formicidae) - Hongjing Zhou; Shuai Yu; Yangming Jiang; Yanju Li; Ziyi Wang; Yonghong Bai; Xiaomei Wu; Meng Lan; Huijun Hu; Keahzn Han; Jun Huang; Yan Li (Applied Animal Behaviour Science, 2025)

Nitrogen utilization in response to cadmium and abscisic acid in rice - Zhi-Jun Xu; Jia-Yi Qu; Meng Zhao; Jing Zhao; Wei-Chi Wang; Jia-Jun Huang; Jia-Shi Peng; Yun-Hua Xiao; Yong-Liang Han; Yan Peng; Bo-Han Liu; Zhen-Xie Yi; et al. (Plant and Soil, 2025)

Nitrogen fixation in Pampinifervens, a new species-rich genus of Aquificaceae that inhabits a wide pH range in terrestrial hot springs - Marike Palmer; Nancy O. Nou; Lara A. Turello; Carolyn E. Power; John C. Ong; Jonathan K. Covington; Dengxun Lai; Xavier Mayali; Anna-Louise Reysenbach; Yan-Ling Qi; Jeremy A. Dodsworth; Jian-Yu Jiao; et al. (Systematic and Applied Microbiology, 2025)

Assessing the methane mitigation potential of biochar and stover incorporation: Insights from the emission dynamics and soil microbiome in maize agroecosystems - Xu Yang; Jun Yuan; Yinghui Bi; Lidan Wang; Junqi Zhang; Chaoqun Wei; Xin Cui; Han Li; Peiyu Luo; Jun Meng; Wenfu Chen (Soil and Tillage Research, 2025)

Conversion of phenol into polymers from wastewater via nonradical peroxydisulfate activation process - Yi-Tong Lv; Xiao-Hui Wang; Jun Cao; Lu Zhang; De-Ming Zhao; Hui-Bing Shi; Wei-Meng Si; Wan-Ju Zhang; Jia Song; Xu Han (Process Safety and Environmental Protection, 2025)

Associations Between Pre- and Post-Diagnosis Dietary Inflammatory Patterns and Ovarian Cancer Survival: Results From the Ovarian Cancer Follow-Up Study - Jia-Xin Liu; Rui-Han Bao; Meng Luan; Chuan Liu; Lang Wu; Fang-Hua Liu; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Qian Xiao; Dong-Hui Huang; Xiao-Ying Li; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Expert consensus on cryosurgery therapy of mucosal melanoma on head and neck - Yadong Wu; Guoxin Ren; Moyi Sun; Zhangui Tang; Longjiang Li; Jian Meng; Zhijun Sun; Shaoyan Liu; Yue He; Wei Shang; Bo Li; Jie Zhang; et al. (Cryobiology, 2025)

Changes in growth and transcriptome expression patterns in mandarin fish (Siniperca scherzeri) under different photoperiods - Jiao Li; Yong Wei; Jun Song; Jun Yang; Xu-Fang Liang; Ke Lu; Qiuling Wang; Ke-Xiang Wang; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; et al. (Acta Oceanologica Sinica, 2025)

Asymmetric C2-functionalization of indoles via visible-light-promoted three-component reaction - Han-Peng Pan; Xiao-Ying Hu; Jun-Hui Luo; Zhao-Jie Fu; Xin-Yi Yao; Meng-Yan Ran; Fang-Xin Wang; Xiang-Zhi Zhang (Molecular Diversity, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Effect of rootstocks on growth potential, soil properties and rhizosphere microbiome of Vitis vinifera L. cv. Cabernet Sauvignon - Ning Shi; Xiao Han; Hao-Cheng Lu; Meng-Bo Tian; Ming-Yu Li; Fei He; Chang-Qing Duan; Ke-Ji Yu; Jun Wang (Plant and Soil, 2025)

Machine learning-based generation of high-resolution 3D full-coverage aerosol distribution data over China using multisource data - Wenze Li; Wenchao Han; Jiachen Meng; Zipeng Dong; Jun Xu; Qimeng Wang; Lulu Yuan; Han Wang; Zhongzhi Zhang; Miaomiao Cheng (Remote Sensing of Environment, 2025)

Mechanistic insight into enhancement of undissolved rice husk biochar on Tetracycline biodegradation by strain Serratia marcescens basing on electron transfer response - Siyu Wang; Jie Han; Ziyi Ge; Xu Su; Yongjia Shi; Fan Xia; Yuwei Huang; Jun Meng (Journal of Hazardous Materials, 2025)

Collaborative regional resistance design for steel frames against progressive collapse: theoretical methods and experimental validation - Yu-hui Zheng; Wei-hui Zhong; Jia Guo; Xu-kai Wang; Bao Meng; Zheng Tan; Shi-chao Duan; Zi-han Wen; Jun Zhao (Engineering Structures, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Correction to: Comparison of Long‑Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2025)

Vertical and lateral bearing performance of bidirectional Helix-Stiffened cement mixing piles on marine soft soil sites: Field tests and numerical simulations - Jun-nan Zhao; Zhong-ling Zong; Yun-han Huang; Meng-meng Lu; De-long Huang; Cheng-yu Guo (Ocean Engineering, 2025)

Dietary supplementation of Litsea cubeba oil promotes growth and intestinal immunity in GIFT tilapia - Fu-Yan Chen; Ying Bai; Gan Yang; Han-Jing Yan; Liu-Yang Li; Zhi-Mou Liu; Ju-Ping Wen; Zhen-Bin Wang; Jun-Hong Xia; Meng-Ling He (Aquaculture, 2025)

The PhoBR two-component system upregulates virulence in Aeromonas dhakensis C4–1 - Wei Feng; Xuesong Li; Nuo Yang; Lixia Fan; Guiying Guo; Jun Xie; Xiuqing Cai; Yuqi Meng; Jifeng Zeng; Yu Han; Jiping Zheng (Aquaculture, 2025)

Nobiletin, an activator of the pyruvate kinase isozyme M1/M2 protein, upregulated the glycolytic signalling pathway and alleviated depressive-like behaviour caused by artificial light exposure at night in zebrafish - Meng-ling Zhang; Xiao-peng Li; Li-fang Gao; Jian Liu; Zi-jun Bi; Yu-han Miao; Yang Shan; Huan-ling Yu (Food Chemistry, 2025)

NIR-driven GOx-like nanozyme-modified injectable thermoresponsive hydrogel for antibacterial therapy and bone regeneration in periodontitis - Changxing Qu; Tianying Luo; Ruxia Han; Dong Mo; Kun Shi; Xicheng Li; Zhongwu Bei; Meng Pan; Songtao Tan; Jun Liu; Zhiyong Qian (Chemical Engineering Journal, 2025)

Roseobacter sinensis sp. nov., a marine bacterium capable to synthesize arachidonic acid - Hong-Chuan Wang; Meng-Han Huang; Dan-Yuan Guo; Wen-Li Liu; Zi-Wen Yang; Dao-Feng Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

Comparison of Long-Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2024)

Melatonin Ameliorates Abnormal Sleep-Wake Behavior via Facilitating Lipid Metabolism in a Zebrafish Model of Parkinson’s Disease - Meng-Zhu Pang; Han-Xing Li; Xue-Qin Dai; Xiao-Bo Wang; Jun-Yi Liu; Yun Shen; Xing Xu; Zhao-Min Zhong; Han Wang; Chun-Feng Liu; Fen Wang (Neuroscience Bulletin, 2024)

Convergence Zone Width Analysis Based on Ray Cluster Theory and Its Application in the Array Depth Optimization of Active Sensors - Zhibin Han; Jun Song; Zhaohui Peng; Lei Meng; Hua Yang; Bing Su (Journal of Ocean University of China, 2024)

Thalassospira aquimaris sp. nov. and Winogradskyella marincola sp. nov. two marine bacteria isolated from an agar-degrading co-culture - Zi-Yue Fu; Dao-Feng Zhang; Meng-Han Huang; Hong-Chuan Wang; Xiao-Ye Chen; Yu-Fang Yao; Yang Yuan; Wen-Jun Li (Antonie van Leeuwenhoek, 2024)

Short-term usage of proton pump inhibitors during admission was associated with increased risk of rehospitalization in critically ill patients with myocardial infarction: a cohort study - Jia-De Zhu; Li-Juan Yang; Jian-Nan Zhao; Ping Wang; Yi-Hua Li; Xue-Sha Zhang; Jian-Mei Pan; Meng-Han Jiang; Hai-Ying Yang; Sun-Jun Yin; Gong-Hao He (European Journal of Clinical Pharmacology, 2024)

Hohaiivirga grylli gen. nov., sp. nov., a New Member of the Family Methylobacteriaceae, Isolated from Cricket (Gryllus chinensis) - Hong-Chuan Wang; Meng-Han Huang; Dan-Yuan Guo; Wei He; Lu Wang; Zi-Yue Fu; Wen-Jun Li; Ai Hua Zhang; Dao-Feng Zhang (Current Microbiology, 2024)

Comparative transcriptome analysis of slow-twitch and fast-twitch muscles in Kazakh horses - Jianwen Wang; Wanlu Ren; Zhiwen Sun; Zixiang Han; Yaqi Zeng; Jun Meng; Xinkui Yao (Meat Science, 2024)

Anti-obesity effects of Lactiplantibacillus plantarum BHP03 on high-fat diet mice and its regulatory function on intestinal microbiota - Jun Meng; Pan-Pan Dong; Meng-Xi Zhu; Zheng Zhang; Jia-Hui Chen; Yue Meng; Chang-He Ding; Han Du; Dong-Ge Zheng; Ling-Guang Du (Food Bioscience, 2024)

Multi-omics insights into the function and evolution of sodium benzoate biodegradation pathway in Benzoatithermus flavus gen. nov., sp. nov. from hot spring - Chao-Jian Hu; Yi-Qing Lv; Wen-Dong Xian; Jian-Yu Jiao; Zheng-Han Lian; Sha Tan; Meng-Meng Li; Zhen-Hao Luo; Ze-Tao Liu; Ai-Ping Lv; Lan Liu; Mukhtiar Ali; et al. (Journal of Hazardous Materials, 2024)

Three new lanostane triterpenoids and two new amides from Alternaria sp. with NLRP3 inflammasome inhibitory activity - De-Wen Bi; Jian- Feng; Wen-Hui Pang; Peng-Yun Yang; Yao-Jun Xu; Muhammad Aurang Zeb; Meng-Ru Wang; Xing-Jie Zhang; Xiao-Li Li; Rui-Han Zhang; Wei-Guang Wang; Wei-Lie Xiao (Natural Product Research, 2024)

Cattle hair as a bioindicator for short- and medium-chain chlorinated paraffin monitoring on cattle farms - Shujun Dong; Su Zhang; Decheng Suo; Xingyi Wu; Xiaoxu Han; Meng Liang; Jun Cao; Yun Zou; Xiaoyan Pei; Peilong Wang (Journal of Hazardous Materials, 2024)

Wave, flow, and suspended sediment dynamics under strong winds on a tidal beach - Lingpeng Meng; Junbiao Tu; Xiaodong Wu; Sha Lou; Jun Cheng; Sergey Chalov; Xiangju Han; Daidu Fan (Estuarine, Coastal and Shelf Science, 2024)

Metal-acid synergistic catalysis accelerates the hydrogen borrowing amination of alcohols by confining Ru sites in Beta zeolite - Yue Wu; Cailing Chen; Zhuo Xiong; Meng Xu; Yue Zhao; Yihu Dai; Yu Han; Yu Zhou; Xiaoling Liu; Jun Wang (Chemical Engineering Journal, 2024)

Combined effects of cadmium and sulfamethoxazole on Eisenia fetida: Insights into accumulation, subcellular partitioning, biomarkers and toxicological responses - Sheng-Nan Zhang; Yi-Tong Zhou; Jun Xia; Yu-Meng Wang; Jun-Wei Ma; Li-Kun Wang; Kashif Hayat; Shan-shan Bai; Cheng-han Li; Ming-Rong Qian; Hui Lin (Science of The Total Environment, 2024)

Ent-eudesmane sesquiterpenoids with anti-neuroinflammatory activity from the marine-derived fungus Eutypella sp. F0219 - Zhong-Ping Jiang; Rui Su; Meng-Ting Chen; Jun-Yi Li; Han-Yu Chen; Lu Yang; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Wan-Shan Li; Yong Rao; Ling Huang (Phytochemistry, 2024)

Nitrogen-doped carbon supported iron nanoparticles for mild catalytic hydrocracking of Xilinguole lignite - Zhi Yang; Fang-Jing Liu; Han-Bing Zhang; Yu-Lu Zhang; Yao Lu; Bo Meng; Shan-Shan Gao; Zai-Xing Huang; Guo-Jun Kang; Jing-Pei Cao; Xian-Yong Wei; Yun-Peng Zhao (Fuel, 2024)

Development of high-performance nitrile hydratase whole-cell catalyst by automated structure- and sequence-based design and mechanism insights - Meng Li; Dong Ma; Jun Qiao; Zhongyi Cheng; Qiong Wang; Zhemin Zhou; Laichuang Han (Systems Microbiology and Biomanufacturing, 2024)

A new biphenanthrene with cytotoxic activity from Liparis nervosa (Thunb.) Lindl - Liang Liu; Qi-Meng Yin; Qi-Jun Dai; Xuan-Yuan Chen; Xi-Qing Chen; Jian-Bin Wang; Han-Qing Pang; Xian-Wen Zhang (Natural Product Research, 2024)

Biotransformation characteristics of tetracycline by strain Serratia marcescens MSM2304 and its mechanism evaluation based on products analysis and genomics - Siyu Wang; Jie Han; Ziyi Ge; Xu Su; Yixuan Chen; Jun Meng (Journal of Environmental Management, 2024)

Biochar application alters soil metabolites and nitrogen cycle-related microorganisms in a soybean continuous cropping system - Xin Cui; Jun Yuan; Xu Yang; Chaoqun Wei; Yinghui Bi; Qiang Sun; Jun Meng; Xiaori Han (Science of The Total Environment, 2024)

Structural analysis of a soluble polysaccharide GSPA-0.3 from the root of Panax ginseng C. A. Meyer and its adjuvant activity with mechanism investigation - Lei Feng; Na Han; Yu-Bo Han; Meng-Wen Shang; Teng-Wei Liang; Zhi-Hui Liu; Si-Kai Li; Jian-Xiu Zhai; Jun Yin (Carbohydrate Polymers, 2024)

Dietary supplementation of patchouli oil improves resistance to Streptococcus agalactiae infection in genetically improved cultured Tilapia (GIFT, Oreochromis niloticus.) as revealed by RNA-Seq - Yin Yi Yao; Zong Xian Zhu; Chun Hui Ai; Xue Ying Liang; Gan Yang; Tong De Liu; Hong Yi Zhang; Han Jing Yan; Jun Hong Xia; Meng Ling He (Aquaculture, 2024)

Sludge pyrolysis integrated biomass gasification to promote syngas: Comparison of different biomass - Aishu Li; Hengda Han; Kaiyue Zheng; Meng Zhu; Kai Xu; Jun Xu; Long Jiang; Yi Wang; Sheng Su; Song Hu; Jun Xiang (Science of The Total Environment, 2024)

Biodegradation of poly(ethylene terephthalate) through PETase surface-display: From function to structure - Wei Han; Jun Zhang; Qi Chen; Yuzhu Xie; Meng Zhang; Jianhua Qu; Yuanji Tan; Yiran Diao; Yixuan Wang; Ying Zhang (Journal of Hazardous Materials, 2024)

Effects of wild boar grubbing on the soil nematode community subject to seasonal variation in a broad-leaved Korean pine forest in Northeast China - Zhong Jie Sun; Heikki Setälä; Ya Xuan Cui; Chen Meng; Ming Ming Cui; Feirong Ren; Shi Jie Han; Jun Qiang Zheng (Forest Ecology and Management, 2024)

Paleozoic and Mesozoic magmatism in the Gaodi porphyry Mo-Cu deposit: Implications for the evolution of the Mongol-Okhotsk Ocean in the northern Great Xing'an Range, NE China - Jing Kan; Ke-Zhang Qin; Le Wang; Kai-Xuan Hui; Ri Han; Noreen J. Evans; Zhao-Jun Meng (Gondwana Research, 2023)

Vineyard soil heterogeneity and harvest date affect volatolomics and sensory attributes of Cabernet Sauvignon wines on a meso-terroir scale - Hao-Cheng Lu; Meng-Bo Tian; Xiao Han; Ning Shi; Hui-Qing Li; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (Food Research International, 2023)

Exopolysaccharide from Bifidobacterium breve alleviate dextran sulfate sodium-induced colitis in mice via inhibiting oxidative stress and regulating intestinal flora - Meng-Meng Niu; Huan-Xin Guo; Jun-Wu Cai; Bo-Fan Duan; Yu-Han Chen; Xiang-Chen Meng (Food Bioscience, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Effects of acid modified biochar on potassium uptake, leaching and balance in an alternate wetting and drying paddy ecosystem - Hongwei Han; Taotao Chen; Chang Liu; Feng Zhang; Yidi Sun; Yikui Bai; Jun Meng; Daocai Chi; Wenfu Chen (Science of The Total Environment, 2023)

Bibliometric analysis of publications on biodegradation of plastics: Explosively emerging research over 70 years - Shan-Shan Yang; Wei-Min Wu; Ji-Wei Pang; Lei He; Meng-Qi Ding; Mei-Xi Li; Yi-Lin Zhao; Han-Jun Sun; De-Feng Xing; Nan-Qi Ren; Jun Yang; Craig S. Criddle; et al. (Journal of Cleaner Production, 2023)

Aroma enhancement of blueberry wine by postharvest partial dehydration of blueberries - Yu Wang; Qi Zhang; Meng-Yao Cui; Yu Fu; Xiao-Han Wang; Qin Yang; Yue Zhu; Xiao-Hui Yang; Hai-Jun Bi; Xue-Ling Gao (Food Chemistry, 2023)

CNIH4 governs cervical cancer progression through reducing ferroptosis - Jun-Yuan Yang; Dong Ke; Yanli Li; Jie Shi; Shi-Meng Wan; An-Jin Wang; Meng-Na Zhao; Han Gao (Chemico-Biological Interactions, 2023)

Microplastics perturb nitrogen removal, microbial community and metabolism mechanism in biofilm system - Tong Wu; Le Zhong; Jie Ding; Ji-Wei Pang; Han-Jun Sun; Meng-Qi Ding; Nan-Qi Ren; Shan-Shan Yang (Journal of Hazardous Materials, 2023)

“Mini-community” simulation revealed the differences of endophytic fungal communities between the above- and below-ground tissues of Ephedra sinica Stapf - Xi Liu; Jin-Long Cui; Zhong-Ya Zhou; Zong-Bao Zhang; Xuan-Ge Cui; Bo Han; Jun-Hong Wang; Meng-Liang Wang; Yi-Min Li (Fungal Biology, 2023)

Phytoecdysteroids from Dianthus superbus L.: Structures and anti-neuroinflammatory evaluation - Xue-Li Hou; Yu-Qi Gao; Jing-Hui Yang; Han-Wu Liu; Meng-Meng Bai; Zhen-Hai Wu; Chun-Huan Li; Jun-Mian Tian; Jin-Ming Gao (Phytochemistry, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Characterization of modified rice straw biochar in immobilizing Bacillus subtilis 168 and evaluation on its role as a novel agent for zearalenone-removal delivery - Jie Han; Jiao Zhang; Jun Meng; Yuanqi Cai; Mo Cheng; Siyu Wu; Zeming Li (Journal of Hazardous Materials, 2023)

Identify nitrogen transport paths and sources contribution in karst valley depression area using isotopic approach - Meng Lu; Fu-Jun Yue; Xiao-Dan Wang; Zi-Han Liu; Zhi-Yu Shi; Ping Zhang (Journal of Environmental Management, 2023)

Hexavalent chromium causes centrosome amplification by inhibiting the binding between TMOD2 and NPM2 - Meng Lu Zhao; Jia Xin Wang; Xue Kai Bian; Jun Zhang; Ya Wen Han; Si Xian Xu; Shao Chin Lee; Ji Zhong Zhao (Toxicology Letters, 2023)

The phosphorus limitation in the post-fire forest soils increases soil CO2 emission via declining cellular carbon use efficiency and increasing extracellular phosphatase - Muhammad Auwal; Han Sun; U.K Adamu; Jun Meng; Lukas Van Zwieten; Bhupinder Pal Singh; Yu Luo; Jianming Xu (CATENA, 2023)

Resveratrol-induced SIRT1 activation inhibits glycolysis-fueled angiogenesis under rheumatoid arthritis conditions independent of HIF-1α - Tian-Tian Jiang; Cong-Lan Ji; Li-Jun Yu; Meng-Ke Song; Yan Li; Qiang Liao; Tuo Wei; Opeyemi Joshua Olatunji; Jian Zuo; Jun Han (Inflammation Research, 2023)

Seeing the forest and the trees: Holistic view of social distancing on the spread of COVID-19 in China - Danlin Yu; Yaojun Zhang; Jun Meng; Xiaoxi Wang; Linfeng He; Meng Jia; Jie Ouyang; Yu Han; Ge Zhang; Yao Lu (Applied Geography, 2023)

Toxicological characteristics of drinking water in two large-scale municipal water supply systems of a metropolitan city in Central China - Huai-Ji Wang; Chen-Wei Peng; Xue Han; Yan Wang; Jie Zhang; Jun-Ling Liu; Meng-Xuan Zhou; Fei Tang; Ai-Lin Liu (Environmental Science and Pollution Research, 2023)

Severe shoot topping slows down berry sugar accumulation rate, alters the vine growth and photosynthetic capacity, and influences the flavoromics of Cabernet Sauvignon grapes in a semi-arid region - Hao-Cheng Lu; Meng-Bo Tian; Ning Shi; Xiao Han; Hui-Qing Li; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (European Journal of Agronomy, 2023)

Drug-Coated Balloon Treatment for Delayed Recanalization of Symptomatic Intracranial Artery Occlusion - Wei Zhao; Xi Chu; Yun Song; Jinping Zhang; Lili Sun; Meimei Zheng; Hao Yin; Jun Zhang; Wei Wang; Yao Meng; Ju Han (Translational Stroke Research, 2023)
Patients with medically refractory non-acute intracranial artery occlusion (ICAO) are difficult to treat. The optimal intervention for these patients is not known. We evaluated the feasibility and safety of drug-coated balloon (DCB) treatment for non-acute ICAO. Consecutive patients with symptomatic medically refractory atherosclerotic non-acute ICAO from January 2015 to July 2021 who underwent DCB treatment were retrospectively analyzed. The rates of stroke, transient ischemic attack, and death within 30 days and the follow-up results were evaluated. A total of 148 patients were enrolled in this study. The 30-day rate of stroke, transient ischemic attack, and death was 8.8%. During the 25.8 ± 15.8-month clinical follow-up period, the rate of outcome beyond 30 days was 4.7%. In the 66 patients with vessel imaging follow-up, 13.6% (9/66) had restenosis. The present study suggests that DCB dilatation is a feasible and effective alternative in carefully selected patients with symptomatic non-acute ICAO.

Identification and characterization of two transcriptional regulators in Xanthomonas oryzae pv. oryzicola YM15 - Xiaoyan Wan; Waqar Ahmed; Jun Yang; Han Meng; Lanfang Wei; Guanghai Ji (Physiological and Molecular Plant Pathology, 2023)

Syn-mineralization hydrous fluid activity in giant Jinchuan magmatic Ni-Cu sulfide deposit in North China Craton - Qing-Han Yuan; Ben-Xun Su; Meng-Meng Cui; Patrick Asamoah Sakyi; Jie-Jun Jing (Lithos, 2023)

Region, vintage, and grape maturity co-shaped the ionomic signatures of the Cabernet Sauvignon wines - Xiao Han; Hao-Cheng Lu; Yu Wang; Xiao-Tong Gao; Hui-Qing Li; Meng-Bo Tian; Ning Shi; Ming-Yu Li; Xiao-Li Yang; Fei He; Chang-Qing Duan; Jun Wang (Food Research International, 2023)

The effect of reservoir expansion from underground karst cave to surface reservoir on water quality in southwestern China - Meng Lu; Xiao-Dan Wang; Fu-Jun Yue; Zi-Han Liu; Zhi-Yu Shi; Ping Zhang (Environmental Science and Pollution Research, 2022)

Climate change attribution of the 2021 Henan extreme precipitation: Impacts of convective organization - Han Qin; Wei Yuan; Jun Wang; Yang Chen; Panxi Dai; Adam H. Sobel; Zhiyong Meng; Ji Nie (Science China Earth Sciences, 2022)

Influence of shrub root combinations and spacing on slope stability: study case at the Yongding River flooding regime, Langfang, China - Ji-Kun Han; Jin-Yong Zhao; Jun Wei; Wen-Yuan Meng; Qi Wang; Jing Zhang; Wei-Jie Wang; Wen-Qi Peng; Heng Zheng (Environmental Science and Pollution Research, 2022)

Wheat genomic study for genetic improvement of traits in China - Jun Xiao; Bao Liu; Yingyin Yao; Zifeng Guo; Haiyan Jia; Lingrang Kong; Aimin Zhang; Wujun Ma; Zhongfu Ni; Shengbao Xu; Fei Lu; Yuannian Jiao; et al. (Science China Life Sciences, 2022)

Rhodoflexus caldus gen. nov., sp. nov., a new member of the phylum Bacteroidota isolated from a hot spring sediment - Ze-Tao Liu; Lan Liu; Wen-Dong Xian; Zheng-Han Lian; Jun-Yi Dai; Bao-Zhu Fang; Meng-Meng Li; Ai-Ping Lv; Zhen-Hao Luo; Jian-Yu Jiao; Wen-Jun Li (Antonie van Leeuwenhoek, 2022)

The Motion and Deformation of Viscoplastic Slide while Entering a Body of Water - Zhenzhu Meng; Xueyou Li; Shoujie Han; Xiao Wang; Jun Meng; Zhipeng Li (Journal of Marine Science and Engineering, 2022)
Landslide-generated waves are hazards that, commonly, exist in the natural world. The motion and deformation of a submerged landslide significantly affect the efficiency of the momentum transfer, between the slide material and the water body, and, thereby, dominate the characteristics of the associated waves. Therefore, investigating how the submerged sliding mass is moved and deformed is of great importance, not only for understanding the physical mechanism behind the slide–water interaction but also for optimizing the predictive models of the wave characteristics. In this study, we assumed the landslide as a viscoplastic fluid and used an ideal viscoplastic material, called Carbopol, to mimic a natural landslide, at the laboratory scale. We, first, determined the coordinates of three control points, including the frontal point, deepest point, and center of mass, so as to quantify the time evolution of the submerged slide motion. We, then, fit the maximums of the coordinates of the control points with an integrated parameter of the incoming landslide, with the support of experimental data. Results indicated that not only the wave features but also the submerged slide motion can be quantified by the slide parameters on impact.

Genome-based reclassification of the genus Meiothermus along with the proposal of a new genus Allomeiothermus gen. nov - Jian-Yu Jiao; Zheng-Han Lian; Ze-Tao Liu; Lan Liu; Meng-Meng Li; Ai-Ping Lv; Wen-Dong Xian; Ting Zhou; Zhitang Lyu; Nimaichand Salam; Wen-Jun Li (Antonie van Leeuwenhoek, 2022)

Maribellus maritimus sp. nov., isolated from marine sediment - Yu-Qi Ye; Ze-Tian Han; Xin-Jiang Liu; Meng-Qi Ye; Zong-Jun Du (Archives of Microbiology, 2022)

Complement C3 Aggravates Post-epileptic Neuronal Injury Via Activation of TRPV1 - Guang-Tong Jiang; Lin Shao; Shuo Kong; Meng-Liu Zeng; Jing-Jing Cheng; Tao-Xiang Chen; Song Han; Jun Yin; Wan-Hong Liu; Xiao-Hua He; Yu-Min Liu; Lanzi Gongga; et al. (Neuroscience Bulletin, 2021)

Association between large artery stenosis, cerebral small vessel disease and risk of ischemic stroke - Fei Han; Ding-Ding Zhang; Fei-Fei Zhai; Jun Xue; Jiang-Tao Zhang; Shuang Yan; Li-Xin Zhou; Jun Ni; Ming Yao; Meng Yang; Ming-Li Li; Zheng-Yu Jin; et al. (Science China Life Sciences, 2021)

Dynamic characteristics and driving factors of vegetation greenness under changing environments in Xinjiang, China - Panxing He; Zongjiu Sun; Zhiming Han; Yiqiang Dong; Huixia Liu; Xiaoyu Meng; Jun Ma (Environmental Science and Pollution Research, 2021)

Degradation mechanism of sludge organic matter treated in alkaline/acidic solution and its effect on long-term strength - Yun-zhi Tan; Meng-jun Han; Rui Ke (Marine Georesources & Geotechnology, 2021)

Molecular epidemiology of enteroviruses associated with severe hand, foot and mouth disease in Shenzhen, China, 2014-2018 - Long Chen; Shao-Jian Xu; Xiang-Jie Yao; Hong Yang; Hai-Long Zhang; Jun Meng; Han-Ri Zeng; Xu-He Huang; Ren-Li Zhang; Ya-Qing He (Archives of Virology, 2020)

Design and Synthesis of Polymer Prodrugs for Improving Water-Solubility, Pharmacokinetic Behavior and Antitumor Efficacy of TXA9 - Yiwen Li; Chun Ye; Chengcheng Cai; Meng Zhao; Na Han; Zhihui Liu; Jianxiu Zhai; Jun Yin (Pharmaceutical Research, 2020)

Chemical content and source apportionment of 36 heavy metal analysis and health risk assessment in aerosol of Beijing - Limeng Cui; Zhuona Wu; Peng Han; Yasuyuki Taira; Huan Wang; Qinghua Meng; Zechen Feng; Shuguang Zhai; Jun Yu; Weijie Zhu; Yuxia Kong; Hongfang Wang; et al. (Environmental Science and Pollution Research, 2020)

Rheological Behavior of Protein Hydrolysates from Papain-treated Male Gonad of Scallop ( Patinopecten yessoensis ) - Jia-Run Han; Jia-Nan Yan; Yi Li; Jun Zhao; Yue Tang; Wen-Gang Jin; Wen-Hui Shang; Meng Zhang; Hai-Tao Wu (Journal of Aquatic Food Product Technology, 2018)

An anti-Propionibacterium acnes antibody shows heterologous resistance to an Actinobacillus pleuropneumoniae infection independent of neutrophils in mice - Jian-fang Liu; Qiu-yue Ma; Ri-ning Zhu; Meng-jun Cheng; Chun-tong Bao; Jing-min Gu; Chang-jiang Sun; Paul Richard Langford; Wen-yu Han; Lian-cheng Lei (Immunologic Research, 2017)

Molecular cloning, expression pattern and phylogenetic analysis of Guanine nucleotide exchange factor Vav2 in lamprey, Lampetra japonica - Yinglun Han; Jun Li; Lei Xu; Qinghua Ma; Meng Gou; Yue Pang; Xin Liu; Qingwei Li (Acta Oceanologica Sinica, 2017)

Agrobacterium deltaense sp. nov., an endophytic bacteria isolated from nodule of Sesbania cannabina - Jun Yan; Yan Li; Xiao Zeng Han; Wen Feng Chen; Wen Xiu Zou; Zhihong Xie; Meng Li (Archives of Microbiology, 2017)

Preparation and In Vitro Evaluation of a MRI Contrast Agent Based on Aptamer-Modified Gadolinium-Loaded Liposomes for Tumor Targeting - Lan-Xin Zhang; Kun-Feng Li; Huan Wang; Meng-Jie Gu; Li-Si Liu; Zhuo-Zhao Zheng; Nan-Yin Han; Zhen-Jun Yang; Tian-Yuan Fan (AAPS PharmSciTech, 2017)

One new lignan derivative from the Combretum alfredii Hance - Meng Bai; Li-Jun Wu; Yue Cai; Shou-Yuan Wu; Xiao-Ping Song; Guang-Ying Chen; Cai-Juan Zheng; Chang-Ri Han (Natural Product Research, 2017)

Bacterial and Archaeal Diversities in Maotai Section of the Chishui River, China - Qingqing Feng; Lu Han; Xu Tan; Yali Zhang; Tianyi Meng; Jun Lu; Jie Lv (Current Microbiology, 2016)

A strategy for introducing an endangered plant Mosla hangchowensis to urban area based on nitrogen preference - Mei-Ying Fan; Kai-Xuan Pan; Wen-Juan Han; Yi-Jun Lu; Qi Shen; Meng Wang; Yuan Ren; Ze-Long Qu; Jie Chang; Ying Ge (Acta Physiologiae Plantarum, 2016)

One new berberine from the branches and leaves of Polyalthia obliqua Hook.f. & Thomson - Li-Jun Wu; Cai-Juan Zheng; Liu-Kai Wang; Chang-Ri Han; Xiao-Ping Song; Guang-Ying Chen; Xue-ming Zhou; Shou-yuan Wu; Xiao-bao Li; Meng Bai; Chun-xin Liu; Jun Yao (Natural Product Research, 2016)

A new cytotoxic biflavonoid from the rhizome of Wikstroemia indica - Meng Shao; Xiao-Jun Huang; Jun-Shan Liu; Wei-Li Han; Hong-Bing Cai; Qing-Fa Tang; Qin Fan (Natural Product Research, 2016)

Direct cloning, expression of a thermostable xylanase gene from the metagenomic DNA of cow dung compost and enzymatic production of xylooligosaccharides from corncob - Ming-zhe Sun; Hong-chen Zheng; Ling-cai Meng; Jun-she Sun; Hui Song; Yun-juan Bao; Hai-sheng Pei; Zheng Yan; Xiu-qing Zhang; Jing-sheng Zhang; Yi-han Liu; Fu-ping Lu (Biotechnology Letters, 2015)

Effect of the Shenfu Injection Combined with Early Goal-Directed Therapy on Organ Functions and Outcomes of Septic Shock Patients - Mao-qin Li; Cui-gai Pan; Xiao-meng Wang; Xun Mo; Zai-xiang Shi; Ji-yuan Xu; Yan-jun Xu; Guan-jie Han (Cell Biochemistry and Biophysics, 2015)

High-throughput sequencing reveals differential expression of miRNAs in tomato inoculated with Phytophthora infestans - Yushi Luan; Jun Cui; Junmiao Zhai; Jie Li; Lu Han; Jun Meng (Planta, 2015)

Isolation and characterization of polymorphic microsatellites in the perennial herb Euphorbia kansui using paired-end Illumina shotgun sequencing - Xiao-Hao Yan; Min-Feng Fang; Zeng-Qiang Qian; Zhan-Lin Liu; Ma-Li Wang; Cai-Ping Tian; Meng-Han Du; Yin-Jun Li; Zhong-Hu Li; Gui-Fang Zhao (Conservation Genetics Resources, 2014)

Sulfur deposition simulations over China, Japan, and Korea: a model intercomparison study for abating sulfur emission - Cheol-Hee Kim; Lim-Seok Chang; Fan Meng; Mizuo Kajino; Hiromasa Ueda; Yuanhang Zhang; Hye-Young Son; Jong-Jae Lee; Youjiang He; Jun Xu; Keiichi Sato; Tatsuya Sakurai; et al. (Environmental Science and Pollution Research, 2012)

Knockdown of zinc finger protein, X-linked (ZFX) inhibits cell proliferation and induces apoptosis in human laryngeal squamous cell carcinoma - Jugao Fang; Zhenkun Yu; Meng Lian; Hongzhi Ma; Jun Tai; Luo Zhang; Demin Han (Molecular and Cellular Biochemistry, 2012)

Long-term simulations of the sulfur concentrations over the China, Japan and Korea: A model comparison study - Cheol-Hee Kim; Lim-Seok Chang; Jeong-Soo Kim; Fan Meng; Mizuo Kajino; Hiromasa Ueda; Yuanhang Zhang; Hye-Young Son; Youjiang He; Jun Xu; Keiichi Sato; Chang-Keun Song; et al. (Asia-Pacific Journal of Atmospheric Sciences, 2011)

β-catenin signaling involves HGF-enhanced HepG2 scattering through activating MMP-7 transcription - Fei-Yan Pan; Sheng-Zhou Zhang; Na Xu; Fan-Li Meng; Hong-Xia Zhang; Bin Xue; Xiao Han; Chao-Jun Li (Histochemistry and Cell Biology, 2010)

Amelioration of hyperglycemia by intestinal overexpression of glucagon-like peptide-1 in mice - Meng-Ju Liu; Jaeseok Han; Young-Sun Lee; Mi-Sung Park; Seungjin Shin; Hee-Sook Jun (Journal of Molecular Medicine, 2010)

Isolation and Characterization of Putative Acetyl-CoA Carboxylases in Arachis hypogaea L. - Meng-Jun Li; Han Xia; Chuan-Zhi Zhao; Ai-Qin Li; Chang-Sheng Li; Yu-Ping Bi; Shu-Bo Wan; Xing-Jun Wang (Plant Molecular Biology Reporter, 2010)

Cloning and sequence analysis of putative type II fatty acid synthase genes from Arachis hypogaea L. - Meng-Jun Li; Ai-Qin Li; Han Xia; Chuan-Zhi Zhao; Chang-Sheng Li; Shu-Bo Wan; Yu-Ping Bi; Xing-Jun Wang (Journal of Biosciences, 2009)